Evaluation Of The Implementation Of The Independent Learning Program For The Independent Campus (Mbkm) At The Faculty Of Economics And Business - Bandar Lampung University: Evaluasi Implementasi Program Merdeka Belajar Kampus Merdeka (Mbkm) Di Fakultas Ekonomi Dan Bisnis - Universitas Bandar Lampung - Defrizal; Vonny Tiara Narundana; Nurdiawansyah nurdiawansyah; Yanuarius Yanu Dharmawan; Appin Purisky redaputri (Borneo Educational Journal (Borju), 2022)
The Independent Learning Program – Independent Campus (MBKM) was launched by the Minister of Education and Culture Nadiem Anwar Makarim in 2020 in order to prepare university graduates who are tough in facing change. The Faculty of Economics and Business, University of Bandar Lampung has implemented the MBKM Program, various kinds of problems in its implementation have certainly been experienced and various efforts have also been made so that this program can run well. The study uses the CIPP jenis (context, input, process and product), research data obtained by using a survey with student respondents who have or are currently participating in the program and students who have not participated in the program totaling 441 respondents. This study was conducted with the aim of evaluating the implementation of MBKM at the Faculty of Economics and Business, University of Bandar Lampung, seen from the perception of students as the main beneficiaries of the program. The results show that the average context dimension is considered very effective, especially from the statement that MBKM activities are very important to face the real world of work, while from the average input dimension it is considered very effective, especially the statement that the study program has facilitated the choice of MBKM activities that can be followed. by students and credit recognition for MBKM activities that are followed is appropriate. So it can be concluded that the MBKM program is appropriate to be implemented in universities to prepare college graduates who are ready to face the world of work, and universities have also facilitated as well as possible.